The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/pharmaceutics15020563
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Preservatives for Protein and Peptide Formulations: An Overview

Abstract: Biological drugs intended for multi-dose application require the presence of antimicrobial preservatives to avoid microbial growth. As the presence of certain preservatives has been reported to increase protein and peptide particle formation, it is essential to choose a preservative compatible with the active pharmaceutical ingredient in addition to its preservation function. Thus, this review describes the current status of the use of antimicrobial preservatives in biologic formulations considering (i) approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…The use of combinations of benzyl alcohol with chlorobutanol and benzyl alcohol with methylparaben may enhance antifungal activity of the formulation compared to the single use of preservatives. The combination of methylparaben and propylparaben increases the antibacterial effect of the preservative system, but also affects the solubility, and enables the protection of both phases of the emulsions [31]. It is speculated that alcohols (benzyl alcohol and pentyl alcohol) exhibit synergistic effects with benzalkonium chloride [32].…”
Section: Discussionmentioning
confidence: 99%
“…The use of combinations of benzyl alcohol with chlorobutanol and benzyl alcohol with methylparaben may enhance antifungal activity of the formulation compared to the single use of preservatives. The combination of methylparaben and propylparaben increases the antibacterial effect of the preservative system, but also affects the solubility, and enables the protection of both phases of the emulsions [31]. It is speculated that alcohols (benzyl alcohol and pentyl alcohol) exhibit synergistic effects with benzalkonium chloride [32].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to our results with AH-adsorbed HPV16 VLPs, mechanistic studies on the structural destabilization effects of APs used in multi-dose formulations of protein therapeutic candidates have been reported on a variety of smaller, globular proteins (in solution), including recombinant human growth hormone [ 21 ], recombinant human interleukin-1 receptor antagonist (rhIL-1ra) [ 20 , 44 ], recombinant human granulocyte colony stimulating factor (rhGCSF) [ 45 ], interferon alpha-2a (IFNA2), and cytochrome c [ 46 , 47 , 48 ]. In these studies, with APs other than TH, the interactions between APs and proteins were hypothesized to occur primarily through non-covalent hydrophobic forces [ 18 , 20 , 44 , 49 ]. Many of these APs (e.g., 2-phenoxyethanol, benzyl alcohol, phenol, methyl/propylparaben, and m-cresol) are phenolic or phenyl derivatives and are thus mostly hydrophobic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Both empirical and statistical (DOE) screening studies with hundreds of candidate multi-dose formulations were then performed. Seven different APs found in approved parenteral products were evaluated [ 6 , 14 , 18 ], both individually and in combination, including chlorobutanol (CB), m-cresol (MC), 2-phenoxyl ethanol (2-PE), benzyl alcohol (BA), phenol, (PH) methylparaben (MP), and propylparaben (PP) [ 15 ]. Stable candidate HPV VLP multi-dose formulations included certain APs (CB, 2-PE, BA, or 2-PE + BA), while other APs (MC, PH, and parabens) displayed suboptimal stability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…If gels are prepared following a straightforward freeze-drying method, cryoaerogel structures can be formulated. Due to the freezing of the gel and the subsequent sublimation to remove the solvent, a highly porous solid structure is obtained [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, a mesoporous tablet-shaped potato starch aerogel was developed as carriers of celecoxib in order to enhance the drug solubility. The obtained data revealed that the prepared aerogels were able to improve the dissolution rate of the loaded celecoxib compared to the pure drug [ 14 ]. In another research study, using the Minitab experimental design software, the major factors for the aerogel synthesis along with optimal values of these parameters were specified.…”
Section: Introductionmentioning
confidence: 99%